Mechanism of escape from nonsense-mediated mRNA decay of human β-globin transcripts with nonsense mutations in the first exon - Neu-Yilik, Gabriele; Amthor, Beate; Gehring, Niels H.; Bahri, Sharif; Paidassi, Helena; Hentze, Matthias W.; Kulozik, Andreas (RNA, 2011)
The degradation of nonsense-mutated β-globin mRNA by nonsense-mediated mRNA decay (NMD) limits the synthesis of C-terminally truncated dominant negative β-globin chains and thus protects the majority of heterozygotes from symptomatic β-thalassemia. β-globin mRNAs with nonsense mutations in the first exon are known to bypass NMD, although current mechanistic models predict that such mutations should activate NMD. A systematic analysis of this enigma reveals that (1) β-globin exon 1 is bisected by a sharp border that separates NMD-activating from NMD-bypassing nonsense mutations and (2) the ability to bypass NMD depends on the ability to reinitiate translation at a downstream start codon. The data presented here thus reconcile the current mechanistic understanding of NMD with the observed failure of a class of nonsense mutations to activate this important mRNA quality-control pathway. Furthermore, our data uncover a reason why the position of a nonsense mutation alone does not suffice to predict the fate of the affected mRNA and its effect on protein expression.
Gesehen am 22.09.2022